Root Cause Analysis on Process Monitoring in Ammonium Sulphate Fertilizer Production - Lam, Heng Loong; Mohd Salleh, Rohayu (Enhanced Knowledge in Sciences and Technology, 2024)
Ammonium sulphate, often known as ZA fertilizer, was extensively employed nitrogen (N) fertilizers for crop cultivation in Malaysia. While ZA fertilizer has been widely used for increased crop yields, concerns about its inconsistent performance despite application have risen. Hence, this study delves into the root causes of this issue. There are two phases in process monitoring which are Phase I implemented 30 subgroups while Phase II implemented 14 subgroups with 5 critical-to-quality, CO2, NH3, ratio of CO2/NH3, specific weight and temperature respectively. Before revealing the root cause, IGV and VV control charts were implemented to monitor the process variability in the production. Process monitoring analysis using IGV and VV charts revealed the VV chart’s superior sensitivity in detecting variations, particularly for the eight samples exhibiting out-of-control signals which are 2nd sample, 5th sample, 6th sample, 10th sample, 11th samples, 12th sample, 13th sample and 14th sample respectively. Further investigation of Root Cause Analysis using TCV on the eight out-of-control signals, it was identified CO2 followed by NH3 as key contributors to these inconsistencies. Hence, CO2 and NH3 need to be focused and solid plans should be developed to address each root cause.